The ultimate guide to internet resources for teachers of gifted students - Karnes, Frances A. (Waco, Texas : Prufrock Press, 2013)
With The Ultimate Guide to Internet Resources for Teachers of Gifted Kids, educators gain a detailed overview of how they can use the Internet to teach new information, extend students' learning, and offer exciting opportunities for differentiation. The authors discuss the many ways in which Internet resources might be used, as well as giving tips on connecting with experts and peers, conducting responsible research, evaluating websites, and more. The book's extensive annotated listing of online resources will make it easy for teachers of gifted kids to plan lessons, enhance students' understanding of material, and encourage students to pursue their academic and extracurricular interests.
Includes bibliographical references.
CoED
Keywords: Gifted children -- Education -- United States -- Handbooks, manuals, etc; Internet in education -- United States; Education -- Computer network resources